A Ratiometric Fluorescence Probe for Selective Visual Sensing of Zn2 - Ajayaghosh, Ayyappanpillai; Carol, Priya; Sreejith, Sivaramapanicker (Journal of the American Chemical Society, 2005)
A simple ratiometric fluorescence probe based on vinylpyrrole end-capped bipyridine for the visual sensing of Zn2+ under aqueous physiological pH (6.8−7.4) is described. The fluorophores 3a−c showed strong emission around 537 nm in acetonitrile with a quantum yield of 0.4. In buffered (HEPES, pH 7.2) acetonitrile−water mixture (9:1 v/v), titration of transition metal salts to 3c showed strong quenching of the emission at 547 nm except in the case of Zn2+, which resulted in a red-shifted emission at 637 nm. Alkali and alkaline earth metal salts could not induce any considerable changes to the emission behavior of 3a−c. The binding of Zn2+ was highly selective in the presence of a variety of other metal ions. Though Cu2+ quenches the emission of 3c, in the presence of Zn2+, a red emission prevails, indicating the preference of 3c toward Zn2+. Job plot and Benesi−Hildebrand analysis revealed a 1:1 complexation between the probe and the metal ion. The selective visual sensing of Zn2+ with a red emission is ideally suited for the imaging of biological specimens.